1971
DOI: 10.1172/jci106606
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vmax in auxotonic systoles from the rate of relative increase of isovolumic pressure: (dP/dt)kP

Abstract: A B S T R A C T High speed oscilloscopic recordings (4000 mm/sec) of left ventricular pressure (micromanometer) and its first derivative were used to calculate contractile element velocity (Vce) during the isovolumic period of auxotonic beats in anesthetized dogs. At 0.5-2.0 msec intervals of isovolumic systole, Vce was derived as (dP/dt)/kP, where k = 24 cm-'. Plots of Vce and P yielded inverse curves from peak Vce to aortic valve opening pressure which averaged 27 msec in controls, and 11 msec during norepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 29 publications
2
23
0
2
Order By: Relevance
“…The same level of pressure which occurred during isometric contraction, before and after each intervention, was used for this calculation and dP/dt and P were determined at that level of pressure. This technique for evaluating the myocardial contractile state has been described in detail previously (12,19,20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same level of pressure which occurred during isometric contraction, before and after each intervention, was used for this calculation and dP/dt and P were determined at that level of pressure. This technique for evaluating the myocardial contractile state has been described in detail previously (12,19,20).…”
Section: Methodsmentioning
confidence: 99%
“…8, 9). (12,19,20,23). The classical studies of A. V. Hill demonstrated that the inverse relationship between the force generated and the velocity of shortening is an important property of skeletal muscle (24).…”
Section: Bilateral Carotid Artery Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…All isolength points were obtained during the first one-third of ejection. In addition, the effects of peak dP/dt and the relations of dP/dt to developed pressure, i.e., (dP/dt) / (P) were examined (32,33). The latter was calculated as the quotient of dP/dt and left ventricular pressure minus end diastolic pressure; the same level of pressure which occurred during the isovolumetric contraction period, before and after ouabain and in the control, anesthetized, and propranolol-treated animals was used for this calculation and dP/dt was always measured at that level of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established that the ICT is important in the assessment of systolic function [16] and the IRT in the assessment of early diastolic function [17]. These intervals correspond to periods of active LV chamber contraction and early relaxation [18].…”
Section: Discussionmentioning
confidence: 99%